HEALTH LITERACY IN NUTRITION AND THE PROMOTION OF HEALTH COMMUNICATION: A SCIENTIOMETRIC STUDY - Gomes de Mello, Priscila (Health and Society, 2024)
Health Literacy (HL) is associated with the acquisition of knowledge, motivation and skills to access, understand, evaluate and apply health information to make choices and decisions about daily health care, disease prevention and health promotion to maintain or improve quality of life. From this perspective, Nutritional Literacy (NL) and Food Literacy (FL) emerge. The objective of this study is to analyze the scientific production through a scientometric study on Health Literacy in Nutrition and the production of Health Communication in this field; and to describe the production on Health Literacy in Nutrition and the Production of Health Communication. This study is of the qualitative and quantitative type developed through a Literature Review and Scientometric study in which articles on the theme of Health Literacy and Health Communication were researched from January 2012 to December 2022 in Clarivate’s Web of Science (WoS). We found 367 references that dealt with Health Literacy and Health Communication, and out of a total of 22 articles, 10 that dealt specifically with the approach to Nutrition and Food were selected. Therefore, the insertion of LN and LA can constitute strategies with potential for effectiveness in health promotion and prevention, when linked to health communication processes. It is necessary to plan new studies in the Brazilian population to analyze the benefits to public health.